2013
DOI: 10.5858/arpa.2011-0628-oa
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor Immunohistochemical Expression Is Associated With Gallbladder Cancer Progression

Abstract: Our results suggest a role for CTGF in GBC progression and a positive association with better prognosis. In addition, they underscore the importance of considering the involvement of inflammation on GBC development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…The present study did not show different CTGF expression in GBC and adjacent NT, or the prognostic value of this biomarker. The role of CTGF in GBC progression and its favorable prognostic impact was earlier reported in a Chilean study 28 . This effect may be attributed to the stromal response to the neoplastic process in an autocrine or paracrine manner 28 .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The present study did not show different CTGF expression in GBC and adjacent NT, or the prognostic value of this biomarker. The role of CTGF in GBC progression and its favorable prognostic impact was earlier reported in a Chilean study 28 . This effect may be attributed to the stromal response to the neoplastic process in an autocrine or paracrine manner 28 .…”
Section: Discussionsupporting
confidence: 54%
“…The role of CTGF in GBC progression and its favorable prognostic impact was earlier reported in a Chilean study 28 . This effect may be attributed to the stromal response to the neoplastic process in an autocrine or paracrine manner 28 . Inconsistent results of both studies may be due to different etiology of GBC in the Latin American and Caucasian populations 3,4,6 .…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, in gallbladder cancer higher expression of CTGF in tumour cells leads to better patient outcomes. CTGF is overexpressed compared to normal gallbladder tissue and increases with advancing tumour stage and high CTGF expression correlates with a better survival outcome in patients with advanced gallbladder cancer . Functional studies have revealed that CTGF increases proliferation of gallbladder cancer cells in vitro , suggesting the microenvironment may be responsible for host‐protective functions …”
Section: Ctgf Expression and Clinical Outcomementioning
confidence: 99%
“…CTGF is a key component of wound repair and has been implicated in tumorigenesis [62, 63]. PLAU encodes the urokinase-type plasminogen activator (uPA) which leads to proteolytic degradation of the extracellular matrix (ECM) [64, 65].…”
Section: Discussionmentioning
confidence: 99%